THE IMPACT OF FAMILY STRUCTURE ON PSYCHOLOGICAL DISTRESS IN DISSOCIATIVE CONVULSIONS - Akhand Pratap Singh; Manish Tyagi; Varnica Kotnala; Prerana Gupta; S. Nagendran (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Dissociative Convulsions (DC), also known as Psychogenic Nonepileptic Seizures (PNES), are episodes resembling epileptic seizures but without abnormal brain activity. This study investigates the relationship between family structure and psychological distress in patients with DC in the Indian context. A cross-sectional design was used to compare psychological outcomes between 72 patients from joint and nuclear families. Standardized measures, including the Dissociative Experiences Scale-II (DES-II), Cognitive Distortions Questionnaire (CD-Quest), Toronto Alexithymia Scale (TAS-20), and Difficulties in Emotion Regulation Scale (DERS-18), were administered. Statistical analyses involved independent t-tests and Pearson’s correlations. Patients from joint families exhibited significantly higher psychological distress, including greater dissociative experiences, cognitive distortions, alexithymia, and emotion regulation difficulties (all p-values < 0.001). These findings highlight the critical role of family dynamics in psychological interventions for DC and underscore the need for culturally sensitive, family-focused treatment approaches.